2020
DOI: 10.1177/0020720920965872
|View full text |Cite
|
Sign up to set email alerts
|

UPCT-Bloopbusters: A methodology of teaching physics and technology concepts using movie scenes and related experiments

Abstract: There is an increasing need for innovative educational methods that can motivate and engage students in subjects that are often perceived as difficult or boring. One such approach is the UPCT-Bloopbusters educational project, developed by a group of professors at the Universidad Politécnica de Cartagena (UPCT), Spain, wherein concepts from the fields of physics and technology are presented and exemplified in the classroom through scenes from different movies in conjunction with experiments. The project was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…The questions were the same for all the subjects involved in this experience: subjects 1, 3, 4, and 2, the latter only for the academic year 2020–21, from Table 1 . The Likert-type questions sought students’ assessment of the new teaching methodology of online practices, as well as their degree of satisfaction [ 41 , 42 ], while the multi-choice question was intended for students to point out what, in their opinions, were the advantages and disadvantages of the new methodology.…”
Section: Tools Used To Assess the New Methodologiesmentioning
confidence: 99%
“…The questions were the same for all the subjects involved in this experience: subjects 1, 3, 4, and 2, the latter only for the academic year 2020–21, from Table 1 . The Likert-type questions sought students’ assessment of the new teaching methodology of online practices, as well as their degree of satisfaction [ 41 , 42 ], while the multi-choice question was intended for students to point out what, in their opinions, were the advantages and disadvantages of the new methodology.…”
Section: Tools Used To Assess the New Methodologiesmentioning
confidence: 99%
“…In addition, the similarity between j h and i H can be calculated using formula (18) in addition to the product, splice, and additive attention calculations with the formula: ( )…”
Section: Attention Mechanismsmentioning
confidence: 99%
“…A virtual physics experiment teaching platform is constructed based on B/S three-layer structure system and MVC mode, and the results show that the constructed platform can better assist students in operating physics experiments through the platform test and student satisfaction analysis. Literature [18] to study the innovation of educational methods, the UPCT-Bloopbusters educational program was carried out in Physics I, Applied Physics and Optical Communication, and by analyzing the success rate and academic results of students before and after applying the new method, the results showed that the educational program could improve the academic performance of students. This paper researches the system integration of information big data and physics teaching, firstly analyzes the current physics teaching status quo from the main performance of the shackles of traditional physics teaching on students and the negative consequences it brings, and designs a physics teaching process model.…”
Section: Introductionmentioning
confidence: 99%